A year in review – evaluating the launch of IJTLD OPEN - H.D. Blackbourn; G.B. Migliori (IJTLD Open)
One year on from the launch of our new open access (OA) journal, IJTLD OPEN, we review its impact. Similar to our flagship journal, the IJTLD, articles published in IJTLD OPEN span a range of topics related to lung health and the majority focus on TB in low- to middle-income countries (LMICs). Interestingly, there has been no lag period in readers accessing the content, with downloads for IJTLD OPEN soon matching and exceeding those for the IJTLD. This demonstrates that OA is helping us to achieve our goal of improving knowledge dissemination in LMICs, where there is restricted access to subscription journals. Citation analysis of the first few issues of IJTLD OPEN also suggests that this higher level of downloads is leading to articles being cited at an accelerated rate.